PENGARUH PENINGKATAN HASIL BELAJAR MODEL TEAMS GAMES TOURNAMENT (TGT) DENGAN MENGGUNAKAN MEDIA ROTAR SD N KALIMULYO 01 - Aulia Piharani, Annisa; Dwi Aryantii, Sekar; Syaffruddin Kuryanto, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Class IV teacher learning activities at SD N Kalimulyo 01 take place using teacher-centered learning methods. During learning, there is a lack of teachers in applying learning models and media to support the achievement of learning objectives. The aim of this research is to analyze the influence of science and science learning outcomes for fourth grade students in elementary schools who are taught using the Team Games Tournament (TGT) learning model based on spinning wheel media. This research uses a quantitative experimental method with a one group pretest-posttest design with a non-probability sampling technique, a saturated sample type. The instrument used is a test instrument which aims to measure student learning outcomes with test questions of 10 multiple choice questions and 5 essay questions. The data analysis techniques used are the paired sample t-test and the N-Gain test. Based on the test results, it was found that the results of the data analysis showed that the Sig. (2-tailed) is 0.000 which is smaller than 0.05 (0.000 < 0.05), so H0 is rejected and Ha is accepted. This result is the expected result because the significance is <0.05, which indicates that there is a difference in the pretest and posttest scores on the science and science learning outcomes. It is known that the results of the hypothesis test show that the teams games tournament (TGT) learning model has an effect on students' science as well learning outcomes.